2021
DOI: 10.33555/jffn.v2i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergy Potential of Averrhoa bilimbi Linn. Fruit Water Extract Shown by Its Suppressive Effect on the Degranulation of RBL-2H3 Cells

Abstract: Allergy rhinitis (AR), as reported by the World Allergy Organization (WAO), is one of the highest prevalence allergies affecting 10-30% of all adults and up to 40% of children. In Indonesia, current evidence showed that the prevalence of AR is increasing. Averrhoa bilimbi Linn. fruit (AF), or locally known as belimbing wuluh, has been scientifically proven to treat many diseases due to the abundant of polyphenol content which was shown to have the potential to treat allergies. Therefore, this study was aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A study was done by Kim, Nam, Rico, & Kang (2012). It is demonstrated that extracts obtained by 70% ethanol from raw and black garlic bulbs exhibited an anti‐allergic effect on rats' basophilic leukemia cells (RBL‐2H3) by inhibiting β‐hexosaminidase (Santoso, Ishida, Nishi, Sugahara, & Putra, 2021). Ethyl acetate extract of BG also has an anti‐allergic impact on immunoglobulin E‐induced allergy reaction to the RBL‐2H3 cells (Yoo, Park, Cho, & Ma, 2019).…”
Section: Bioactivity Of Black Garlicmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was done by Kim, Nam, Rico, & Kang (2012). It is demonstrated that extracts obtained by 70% ethanol from raw and black garlic bulbs exhibited an anti‐allergic effect on rats' basophilic leukemia cells (RBL‐2H3) by inhibiting β‐hexosaminidase (Santoso, Ishida, Nishi, Sugahara, & Putra, 2021). Ethyl acetate extract of BG also has an anti‐allergic impact on immunoglobulin E‐induced allergy reaction to the RBL‐2H3 cells (Yoo, Park, Cho, & Ma, 2019).…”
Section: Bioactivity Of Black Garlicmentioning
confidence: 99%
“…A study was done by Kim, Nam, Rico, & Kang (2012). It is demonstrated that extracts obtained by 70% ethanol from raw and black garlic bulbs exhibited an anti-allergic effect on rats' basophilic leukemia cells (RBL-2H3) by inhibiting βhexosaminidase (Santoso, Ishida, Nishi, Sugahara, & Putra, 2021).…”
Section: Anti-allergy Activitymentioning
confidence: 99%